EVALUATION OF 17 MEDICINAL PLANTS FROM NORTHERN CÔTE D’IVOIRE FOR THEIR IN VITRO ACTIVITY AGAINST STREPTOCOCCUS PNEUMONIAE - Kone, Witabouna Mamidou; Kagoyire, Kamanzi Atindehou; Adèle, Kacou-N'Douba; Mireille, Dosso (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
A total of 20 Côte d’Ivoire plant extracts, belonging to 17 different species out of 11 families, were investigated for their antibacterial activity against Streptococcus pneumoniae (Pneumococcus). The plants were selected on the base of their ethnomedicinal use, in Northern Côte d’Ivoire, against various infections such as upper track diseases. From all the crude extracts tested, only 7 from 6 plant species showed a promising in vitro bactericidal activity against peumococcus, some of which were resistant to penicillin. The most active extracts were from Erythrina senegalensis (Fabaceae), Piliostigma thonningii (Caesalpiniaceae), Waltheria indica (Sterculiaceae), Andira inermis (Fabaceae), Uapaca togoensis (Euphorbiaceae), Keetia hispida (Rubiaceae) and Combretum molle (Combretaceae). This is the first report of the antipneumococcal activity of the tested plant species. The results of this preliminary investigation support the traditional use of the active plants in the treatment of pneumococcal infections. The most active could be candidates for isolation of compounds which could develop into new lead structures for drugs against Streptococcus pneumoniae